2023
DOI: 10.1002/admi.202202503
|View full text |Cite
|
Sign up to set email alerts
|

19 nm‐Thick Grafted‐To Polymer Brushes onto Optimized Poly(Dopamine)‐Coated Surfaces

Abstract: to carefully consider the interactions of the device's interfaces with the complex media it is subjected to. The type of interactions and their extent can be effectively controlled by modification of the surface using polymer chains. Polymer brush coatings, in particular, can be employed to introduce specific surface properties with great accuracy due to extensive control over variables such as brush thickness, grafting density, polymer architecture, and functional groups. [4][5][6] Polymer brush coatings have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Poly­(dopamine) deposition was performed by dip-coating of the substrates in a solution of dopamine in NaOAc buffer (pH 7) in the presence of oxidizing agent NaIO 4 . The deposition reaction was performed until approximately 10 nm of poly­(dopamine) could be measured on gold and SiO 2 by spectroscopic ellipsometry (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poly­(dopamine) deposition was performed by dip-coating of the substrates in a solution of dopamine in NaOAc buffer (pH 7) in the presence of oxidizing agent NaIO 4 . The deposition reaction was performed until approximately 10 nm of poly­(dopamine) could be measured on gold and SiO 2 by spectroscopic ellipsometry (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Using the insights developed in the above studies, our group developed an approach to overcome the aforementioned limitations. In previous studies, we have presented a two-step grafting-to procedure that consists of poly­(dopamine) deposition on SiO 2 followed by grafting of poly­(GMA)- b -poly­(NIPAM) block copolymers. , In contrast to the two coating strategies described above, we demonstrated that our procedure could achieve polymer brush coatings of appreciable grafting density, and with thicknesses to 19 nm. In these studies, we demonstrated the grafting of block copolymers of varying sizes and the effect on the resulting thermoresponsive and antifouling properties of the produced poly­(GMA)- b -poly­(NIPAM) brushes .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation